HISTORY OF COLONIAL MEDICAL AND HEALTH SERVICES IN IBADAN 1900 – 1960 (2014)
The provision of modern health services was a legacy of colonial administration in Africa. Yet, little attention has been paid to the history of medical and health development in Africa, especially Ibadan, which benefited greatly from the colonial health policy. This study, therefore, examined the changing trends in the growth and development of colonial medical and health services in Ibadan between 1900 and 1960 with a view to highlighting the impact of colonial medicine in the city. Adopting an ethnographic design, the study utilised archival and oral sources. The former was obtained from the National Archives, Ibadan. It included Chief Secretary’s Office Papers, Oyo Provincial Papers, Oyo Divisional Papers, Ibadan Divisional Papers, Yoruba News, 1924 – 1945; Daily Times, 1926 – 1960; Daily Service, 1933 – 1960 and Southern Nigeria Defender, 1944 – 1960. The latter comprised in-depth interviews with 35 people, ages 50 to 95, selected through a snowball approach and purposive sampling. The sample comprised traditional healers (10), Western-trained medical doctors (6), nurses (6) community elders (6), university lecturers (5), and civil servants (2). Data were subjected to historical analysis. Colonial health services in Ibadan evolved in consequence of European health needs. These services were later extended to the local people due to the indispensability of indigenous labour to the running of the colonial state. With the opening of Jericho European Hospital (1900), Oranyan Dispensary (1901), Agodi Dispensary (1920) and Adeoyo Hospital (1927), the elite demonstrated enthusiasm in hospital treatment due to their exposure. A majority of the natives shunned medical amenities because of their negative perception of colonial medicine. Yet, hospital patronage for treatment of infectious diseases such as typhoid fever, yellow fever, guinea worm and non-infectious diseases, like hernia and asthma, increased from 590 (1928) to 12,351 (1945). This development was connected with colonial propaganda on hospital medication. The period also witnessed vaccination campaign against smallpox and introduction of maternal and child health services at Adeoyo, Elekuro, Aremo and Agbongbon which had positive impact on childhood mortality. Equally, building of public latrines (148), incinerators (50), and slaughter slabs (8) were some of the health measures carried out. However, hundreds of people did not have access to these amenities; overcrowding with insufficient beds, shortage of clinical personnel and drugs also characterised hospital services. This situation provoked virulent criticism of the colonial administration by the elite. They demanded more modern health services. Colonial administration partially responded (1946) with a Ten-Year-Medical and Health Development Plan which affected the whole country. This situation became consolidated with the introduction of free medical services by the Western Regional Government (1954). The opening of the University College Hospital (1957) and the inception of Ibadan Government Chest Clinic (1959) further enhanced expansion of health services. Yet, these facilities were largely concentrated in the city of Ibadan. Up till 1960, medical and health services were non-existent in the villages. Colonial medical and health services which evolved between 1900 and 1960 occasioned a fair improvement in the medical condition and health status of the people of Ibadan. Therefore, colonial medicine in Ibadan was, overall, partially effective